MEIOFAUNA COMMUNITY IN THE COASTAL AREA OF THE SUNGAI KUNYIT, MEMPAWAH REGENCY, WEST KALIMANTAN PROVINCE - Hadinata, Fitra Wira; Ariansyah, Ariansyah; Soetignya, Widadi Padmarsari (Politeknik Kelautan dan Perikanan Dumai, 2023)
The Sungai Kunyit Coastal Area has a multipurpose and strategic role in supporting the economic development of the community in the West Kalimantan area. This research was conducted to analyze the value of the ecological index of meiofauna and water quality in the coastal area of the Kunyit River, Mempawah Regency. Study this expected could give description condition environment in the Turmeric River Coastal Area for utilization and management in a manner sustainable . Study this conducted for 3 months , namely in the month August until October 2022 in the Turmeric River Coastal Area Regency Mempawah with line transect method . Sample taken from three station . Analysis sample carried out in the Laboratory Management Resource waters and carried out a correlation test for knowing connection structure meiofauna community and conditions environment . Based on results study there were 11,787 ind /m³ of meiofauna during research . density ranges from 10-99 ind /m³, index diversity average 2.20, index uniformity >0.6, index dominance 0.14 <1 close to zero. Based on correlation test results is known that there is a relationship between structure meiofauna community and waters conditions.